Desafios perigosos do Youtube: considerações sobre o risco transformado em espetáculo - Miranda, Luisa Maria Freire (2020)
The evolution of the information and communication technologies (ICT) and the growing popularization of digital media have generated profound changes in the way people relate and decide to enunciate themselves in the contemporary world. In this context, YouTube is considered as an emblematic device for displaying online content by sharing videos produced by its own users. Amid an infinity of videos hosted by this platform, there are the Youtube challenges (YC) - videos, mostly homemade, that bring as a central proposal the registration of a practice called “challenge”. Some of the YC propose the execution of a kind of dangerous play, consisting of activities that, despite their playful and entertaining character, can result in health risks or even lead to the death of their practitioners, who are mostly children and adolescents. This research aims to problematize YC as materiality of a risk modality that, among other elements, brings as corollary modes of enunciation guided by the online exposure of risk practices as a form of entertainment. We therefore questioned whether the concept of risk-spectacle presented by Spink (2012) is a possible way to think about the form of risk present in these productions. Regarding the theoretical-methodological dimension used, we choose the Foucault's Analysis of discourse, as well as authors such as Fischer, Spink, Hall, Miranda, Sampaio, Sibilia, which underpinned our discussions. The material in our analysis consisted of five challenges: fainting challenge; cinnamon challenge; challenge fire; aerosol challenge and condom challenge, which are presented, each of them, in two videos - one with the highest number of views on the surveyed date and the other with the lowest number of views - totaling the number of 10 videos analyzed. In addition, the 20 most recent comments of each video were presented in order to make visible how Internet users interact with the videos creators. The investigation of the listed materials was made based on the formal and structural aspects of the recordings, as well as on their comments, which served as categories for analyzing the challenges of youtube. Through them, we conclude that the videos presented characteristics related to the risk-spectacle enunciative field, such as: the form of dialogue with viewers similar to the television format; the explanation of the step-by-step to carry out the challenges; the qualification of the practice as something that presents risk, but also that is a source of fun; the request for likes and shares of the video. Thus, the risk presented in these practices is articulated around some aspects such as: the search for visibility (online) and forms of entertainment that occur through a body placed in suffering and under imminent risk of mutilation, causing, as a result, deaths and accidents.